Hör-Sehen Strategy to Improve Text Understanding in Learning German for Beginners - Marantika, Juliaans E.R; Tomasouw, Jolanda; Wenno, Eldaa Crystle; Noya van Delzen, June Carmen (Makassar State University, 2023)
Abstract. This study investigates the use of the Hör-Sehen strategy in improving students' ability to understand texts in the Receptive course of the German language. This strategy combines what is heard and what is seen (e.g. an audio-visual technique), making it easier for students to understand the content of the text. This research used a mixed methods research design, combining descriptive quantitative and qualitative methods of a Concurrent embedded research model. The data collection techniques used in this study consisted of observation, pre-test implementation, experiment implementation, post-test implementation, questionnaire distribution, and student response questionnaire. Respondents in this study amounted to 30 students of the German language education study program who were at the beginner level. The results show that applying the Hör-Sehen strategy has a statistically significant positive influence on the ability to understand German texts in beginning learners in the Receptive course. The results of the interviews and questionnaires show that using this strategy can focus students' thinking and make them interested and motivated to take part in the learning process. The other results show that the students understand the information contained in the texts, can offer an interpretation, and provide reflection and assessment of a text through exercises and assignments, which are structured according to the steps in this strategy and form an initial understanding of difficult vocabulary in the textKeywords: Language Ability, Text Understanding, Beginning Language Learners, German, Hör-Sehen Strategy